Time Budget Pressure dan Audit Quality dengan Komitmen Profesional dan Supervisi Audit sebagai Variabel Moderasi - Padmawati, Ni Putu Ida Rahayu; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
This study aims to obtain empirical evidence of the effect of time budget pressure on audit quality with professional commitment and audit supervision as moderating variables for auditors at public accounting firms registered in Bali Province. The sampling technique used is purposive sampling and obtained as many as 54 respondents. The study used data analysis techniques with Moderated Regression Analysis (MRA). Research shows that time budget pressure has a negative effect on audit quality, organizational commitment and audit supervision are able to weaken the effect of time budget pressure on audit quality at public accounting firms in Bali Province. This means that the higher the time budget pressure, the lower the audit quality, and the higher the professional commitment of an auditor and the existence of audit supervision quality. Keywords: Time Budget Pressure; Professional commitment; Audit Supervision; Audit Quality.